A structural MRI study of excoriation (skin-picking) disorder and its relationship to clinical severity. (30th November 2017) - Harries, Michael D.; Chamberlain, Samuel R.; Redden, Sarah A.; Odlaug, Brian L.; Blum, Austin W.; Grant, Jon E.
Abstract: Excoriation (skin-picking) disorder (SPD) shares symptomology with other obsessive-compulsive and related disorders. Few studies, however, have examined the neurological profile of patients with SPD. This study examined differences in cortical thickness and basal ganglia structural volumes between 20 individuals with SPD and 16 healthy controls using magnetic resonance imaging (MRI). There were no significant differences in demographic variables (age, gender, education and race) between groups. All subjects completed a structural MRI scan and completed a battery of clinical assessments focusing on SPD symptom severity, depression and anxiety symptoms, and quality of life. No statistically significant differences in basal ganglia (caudate, putamen, and nucleus accumbens) structural volumes were found between groups. In individuals with SPD, increasing impulsiveness correlated positively with increased cortical thickness in the left insula, and skin picking severity correlated negatively with cortical thickness in the left supramarginal gyrus and a region encompassing the right inferior parietal, right temporal and right supramarginal gyrus. This study suggests similarities and differences exist in symptomology between SPD and the other obsessive-compulsive and related disorders. Additional neuroimaging research is needed to better delineate the underlying neurobiology of SPD. Highlights: Inclusion of SPD as OCD-related disorder in DSM V is partially supported. SPD severity relates to increased cortical thickness in left insula. SPD severity relates to lower cortical thickness in temporal and parietal areas. Potential differences in pathophysiology of SPD and OCD are discussed. The study does not confirm a role for the basal ganglia in SPD.